Method for producing powder dispersions and composites

JP2026169282APending Publication Date: 2026-10-16AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2026177011
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-15
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、分散安定性、ハンドリング性、および長期保管性を具備した、テトラフルオロエチレン系ポリマーのパウダー分散液が得られる。また、本発明によれば、電気物性等のテトラフルオロエチレン系ポリマーの物性を高度に具備するとともに、表面平滑性等の物性に優れた焼成物を有する複合体が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169282000001
    Figure 2026169282000001
  • Figure 2026169282000002
    Figure 2026169282000002
Patent Text Reader

Abstract

To provide a powder dispersion containing a tetrafluoroethylene polymer, a predetermined polyoxyalkylene-modified polydimethylsiloxane, and a liquid dispersion medium, and a composite having a calcined product that highly possesses the physical properties of a tetrafluoroethylene polymer. [Solution] The powder dispersion of the present invention comprises a tetrafluoroethylene polymer powder, a liquid dispersion medium, and a polyoxyalkylene-modified polydimethylsiloxane having a weight-average molecular weight of 3000 or less and an HLB value of 1 to 18 calculated from the Griffin formula. The composite of the present invention can be produced by applying the powder dispersion of the present invention to a surface and heating it.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing powder dispersions and composites. [Background technology]

[0002] Printed circuit boards used for transmitting high-frequency signals require excellent transmission characteristics. Tetrafluoroethylene polymers, which have low dielectric constant and dielectric loss tangent, are attracting attention as insulating layer materials for printed circuit boards with high transmission characteristics. A powder dispersion containing tetrafluoroethylene polymer powder and a liquid dispersion medium is known as a material for forming an insulating layer containing such polymers. Tetrafluoroethylene polymers generally have low surface tension, and their powders have poor dispersibility. To improve the dispersion stability of powder dispersions, Patent Documents 1, 2, and 3 propose formulations of specific surfactants, respectively. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2009-161616 [Patent Document 2] Japanese Patent Publication No. 2012-082437 [Patent Document 3] International Publication No. 2014 / 010968 [Overview of the project] [Problems that the invention aims to solve]

[0004] However, such powder dispersions tend to foam easily, making them difficult to handle when compounding them, mixing them with other components such as resin varnishes, or applying them as coatings. Furthermore, long-term storage of such dispersions required controlling their liquid properties, such as pH, viscosity, and uniformity. Furthermore, obtaining powder dispersions with excellent physical properties and dispersion stability often requires other additives, making their preparation complicated. This problem was particularly pronounced when using silicone-based surfactants or highly fibrillated polytetrafluoroethylene powders.

[0005] Furthermore, when calcined products were produced from such powder dispersions, the residual or decomposed surfactants tended to impair the physical properties of the calcined products, such as their electrical properties or surface smoothness. The object of the present invention is to provide a powder dispersion with excellent dispersion stability, handling properties, and long-term storage capabilities. A composite having a calcined product with excellent physical properties based on a tetrafluoroethylene polymer can be easily produced from such a powder dispersion. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A powder dispersion comprising a tetrafluoroethylene polymer powder, a liquid dispersion medium, and a polyoxyalkylene-modified polydimethylsiloxane having a weight-average molecular weight of 3000 or less and an HLB value of 1 to 18 calculated from the Griffin formula. [2] The powder dispersion of [1], wherein the static surface tension of the polyoxyalkylene-modified polydimethylsiloxane is 28 mN / m or less. [3] A powder dispersion of the [1] or [2], wherein the dynamic surface tension of the polyoxyalkylene-modified polydimethylsiloxane is 40 mN / m or less. [4] A powder dispersion of any of the above [1] to [3], wherein the polyoxyalkylene-modified polydimethylsiloxane has an HLB value of 10 to 16. [5] A powder dispersion of any of the [1] to [4] above, wherein the molecular weight dispersion of the polyoxyalkylene-modified polydimethylsiloxane is less than 2.0. [6] A powder dispersion of any of the above [1] to [5], wherein the polyoxyalkylene-modified polydimethylsiloxane has a degree of polymerization of oxyalkylene groups from 2 to 100 and a degree of polymerization of dimethylsiloxane from 2 to 100. [7] A powder dispersion of any of the above [1] to [6], wherein the polyoxyalkylene-modified polydimethylsiloxane is a polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in the main chain and oxyalkylene groups in the side chains. [8] A powder dispersion of any of the above [1] to [6], wherein the polyoxyalkylene-modified polydimethylsiloxane is a polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in the main chain and oxyalkylene groups at the ends of the main chain. [9] A powder dispersion of any of the above [1] to [8], wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer that contains units based on perfluoro(alkyl vinyl ether), with the units based on perfluoro(alkyl vinyl ether) comprising 1 to 5 mol% of the total units, and has a melting temperature of 260 to 320°C.

[10] A powder dispersion according to any of the above [1] to [9], wherein the powder comprises a first powder of polytetrafluoroethylene and a second powder of a tetrafluoroethylene polymer having a melting temperature of 260 to 320°C, and containing units based on perfluoro(alkyl vinyl ether), with the units based on perfluoro(alkyl vinyl ether) being 1 to 5 mol% of the total units, and the proportion of the second powder to the sum of the first and second powders being 25% by mass or less.

[11] A powder dispersion of any of the above [1] to

[10] , further comprising at least one nonionic surfactant selected from the group consisting of ester-type surfactants, ether-type surfactants, ester-ether-type surfactants, alkanolamide-type surfactants, alkyl glycosides, and higher alcohols.

[12] A powder dispersion of any of the [1] to

[11] , wherein the liquid dispersion medium contains water.

[13] The powder dispersion liquid according to the above

[12] , wherein the pH of the powder dispersion liquid is from 6 to 12.

[14] A powder dispersion liquid having a viscosity of less than 400 mPa·s, comprising: tetrafluoroethylene-based polymer powder; a polyoxyalkylene-modified polydimethylsiloxane that contains dimethylsiloxane units in its main chain and has oxyalkylene groups in its side chains, or a polyoxyalkylene-modified polydimethylsiloxane that contains dimethylsiloxane units in its main chain and has oxyalkylene groups at its main chain terminals; and a liquid dispersion medium containing at least water.

[15] A method for producing a composite, comprising coating the surface of a base material with the powder dispersion liquid according to any one of the above [1] to

[14] , and heating the coated base material to produce a fired product of the tetrafluoroethylene-based polymer, thereby obtaining the composite having the base material and the fired product. Effects of the Invention

[0007] According to the present invention, a tetrafluoroethylene-based polymer powder dispersion liquid having dispersion stability, handleability, and long-term storage properties can be obtained. Further, according to the present invention, a composite having a fired product that highly possesses the physical properties of the tetrafluoroethylene-based polymer such as electrical properties, and is excellent in physical properties such as surface smoothness can be obtained. Modes for Carrying Out the Invention

[0008] The following terms have the following meanings. "Average particle diameter (D50)" is the volume-based cumulative 50% diameter of an object such as powder or filler, determined by a laser diffraction / scattering method. That is, the particle size distribution is measured by a laser diffraction / scattering method, a cumulative curve is determined with the total volume of the particle population taken as 100%, and the particle diameter at the point where the cumulative volume reaches 50% on the cumulative curve is defined as the average particle diameter. "Melting temperature" is the temperature corresponding to the maximum value of the melting peak of a polymer measured by a differential scanning calorimetry (DSC) method. "Glass transition point (Tg)" is a value measured by analyzing a polymer with a dynamic viscoelasticity measurement (DMA) method. "Viscosity of powder dispersion" refers to the viscosity measured using a B-type viscometer under the conditions of 25°C and a rotation speed of 60 rpm. The measurement is repeated 3 times, and the average value of the three measured values is taken. "Thixotropy ratio of powder dispersion" is a value calculated by dividing the viscosity measured at a rotation speed of 30 rpm by the viscosity measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated 3 times, and the average value of the three measured values is taken. "Specific surface area of powder" is a value calculated by measuring the powder using the gas adsorption (constant volume method) BET multi-point method, and can be determined using NOVA4200e (manufactured by Quantachrome Instruments). "Weight average molecular weight of polyoxyalkylene-modified polydimethylsiloxane" is determined as the polystyrene-equivalent weight average molecular weight in gel permeation chromatography (GPC) analysis. "HLB value of polyoxyalkylene-modified polydimethylsiloxane" is a value calculated by the Griffin formula, and is determined by multiplying by 20 the value obtained by dividing the molecular weight of the polyoxyalkylene moiety in the molecule by the molecular weight of the organopolysiloxane. "Static surface tension" is determined by the Wilhelmy method using an automatic surface tensiometer Model CBVP-Z (manufactured by Kyowa Interface Science Co., Ltd.) with a 0.1 mass% aqueous solution of polyoxyalkylene-modified polydimethylsiloxane. "Dynamic surface tension" refers to the dynamic surface tension of a 0.1 mass% aqueous solution of polyoxyalkylene-modified polydimethylsiloxane at 25°C under the maximum bubble pressure method with a bubble generation period of 6 Hz, and is a value measured by immersing the sensor of a dynamic surface tensiometer Theta t60 manufactured by Eko Seiki Co., Ltd. in the aqueous solution. The term "unit" in a polymer means an atomic group based on the monomer formed by polymerization of the monomer. The unit may be a unit directly formed by a polymerization reaction, or may be a unit in which a part of the unit is converted to another structure by treating the polymer. Hereinafter, the unit based on monomer a is also simply referred to as "monomer a unit".

[0009] The powder dispersion of the present invention (hereinafter also referred to as "this dispersion") is a dispersion in which the F powder is dispersed in particulate form, comprising a tetrafluoroethylene polymer (hereinafter also referred to as "F polymer") powder (hereinafter also referred to as "F powder"), a liquid dispersion medium, and a polyoxyalkylene-modified polydimethylsiloxane having a weight-average molecular weight of 3000 or less and an HLB value of 1 to 18 calculated from the Griffin formula. The polyoxyalkylene-modified polydimethylsiloxane is a nonionic compound.

[0010] This dispersion offers excellent dispersion stability, handling properties, and long-term storage capabilities. The calcined product formed from this dispersion exhibits superior physical properties based on tetrafluoroethylene polymers, such as electrical properties, and also boasts excellent surface smoothness. The reason is not entirely clear, but it can be considered as follows. When nonionic surfactants are used in a dispersion of F powder, they interact with the surface of the F powder, improving its dispersion stability. However, they also tend to accumulate on the surface of the dispersion, weakening its surface tension. This can lead to a deterioration in the defoaming properties of the dispersion, reduced handling, and decreased mixability with other materials. In particular, silicone-based surfactants, due to their molecular structure, generally do not interact sufficiently with F powder, and the aforementioned tendency tends to be more pronounced. For example, in order to achieve dispersion stability of F powder, it is necessary to increase its amount, which inevitably leads to a decrease in the handling and mixability of the dispersion.

[0011] On the other hand, the polyoxyalkylene-modified polydimethylsiloxane in this dispersion is a nonionic compound with a small weight-average molecular weight and an HLB value within a predetermined range, and can be described as a silicone-based surfactant with a highly balanced hydrophobicity and hydrophilicity. The polyoxyalkylene-modified polydimethylsiloxane has a short polymer chain length and is likely to readily cover the surface of the F powder, thus promoting enhanced interaction with the F powder. In other words, because the polyoxyalkylene-modified polydimethylsiloxane adheres highly to the F powder, the dispersion stability is selectively improved in this dispersion, and the deterioration of liquid properties is suppressed. Furthermore, polyoxyalkylene-modified dimethylsiloxanes with a low weight-average molecular weight exhibit excellent thermal decomposition properties, making them easily decomposed when the dispersion is heated to form calcined products. As a result, the calcined products tend to possess a high degree of physical properties based on F polymers.

[0012] The F polymer in this invention is a polymer containing units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units"). The F polymer may be thermally fused or non-thermally fused. The melting temperature of the heat-meltable F polymer is preferably 180°C or higher, more preferably 200 to 325°C, and even more preferably 260 to 320°C. The melt viscosity of polymer F at 380°C is 1 × 10⁻⁶. 2 From 1 x 10 6 Pa·s is preferable. The glass transition temperature of the F polymer is preferably 30 to 150°C, and more preferably 75 to 125°C. The fluorine content of the F polymer is preferably 70% by mass or more, and more preferably 72 to 76% by mass.

[0013] Examples of F polymers include polytetrafluoroethylene (hereinafter also referred to as "PTFE"), polymers containing TFE units and ethylene-based units (hereinafter also referred to as "ETFE"), polymers containing TFE units and propylene-based units, polymers containing TFE units and perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE")-based units (hereinafter also referred to as "PAVE units") (hereinafter also referred to as "PFA"), polymers containing TFE units and hexafluoropropylene (hereinafter also referred to as "HFP")-based units (hereinafter also referred to as "FEP"), polymers containing TFE units and fluoroalkylethylene-based units, and polymers containing TFE units and chlorotrifluoroethylene-based units, with PFA or FEP being preferred, and PFA being more preferred. The polymer may further contain units based on other comonomers. Examples of PTFE include low molecular weight PTFE and modified PTFE. Note that low molecular weight PTFE and modified PTFE also include copolymers of TFE with trace amounts of comonomers (HFP, PAVE, FAE, etc.). For PAVE, CF2=CFOCF3, CF2=CFOCF2CF3, or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE") are preferred, with PPVE being more preferred.

[0014] The F polymer preferably has oxygen-containing polar groups. In this case, the dispersion tends to have excellent dispersion stability, and the fired product such as the polymer layer obtained from the dispersion tends to have excellent physical properties such as electrical properties, surface smoothness, and adhesion. The oxygen-containing polar group may be contained in monomer units in the F polymer, or it may be contained in terminal groups of the main chain of the F polymer. An example of the latter is an F polymer having the oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc. The oxygen-containing polar group is preferably a hydroxyl group-containing group or a carbonyl group-containing group, and more preferably a carbonyl group-containing group.

[0015] The hydroxyl group-containing group is preferably a group containing an alcoholic hydroxyl group, and more preferably -CF2CH2OH or C(CF3)2OH. The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, alkoxycarbonyl group, amide group, isocyanate group, carbamate group (-OC(O)NH2), acid anhydride residue (-C(O)OC(O)-), imide residue (-C(O)NHC(O)-, etc.), or carbonate group (-OC(O)O-), with acid anhydride residue being more preferred. If the F polymer has carbonyl group-containing groups, the number of carbonyl group-containing groups in the F polymer is 1 × 10⁶ carbon atoms in the main chain. 6 The number of carbonyl groups per molecule is preferably 10 to 5000, more preferably 50 to 4000, and even more preferably 100 to 2000. In this case, the dispersion tends to have excellent dispersion stability, handling properties, and long-term storage properties. The number of carbonyl group-containing groups in polymer F can be quantified by the polymer composition or by the method described in International Publication No. 2020 / 145133.

[0016] The F polymer is preferably a tetrafluoroethylene-based polymer containing PAVE units, with PAVE units present in 1 to 5 mol% of the total units, and having a melting temperature of 260 to 320°C. More preferably, it is a polymer (1) containing PAVE units, with PAVE units present in 1.5 to 3 moles of the total monomer units, and having oxygen-containing polar groups, or a polymer (2) containing PAVE units, with PAVE units present in 2 to 5 mol% of the total monomer units, and not having oxygen-containing polar groups. These polymers form microspherulites in the fired product such as a polymer layer, which tends to improve the properties of the resulting fired product.

[0017] Polymer (1) is preferably a polymer containing TFE units, PAVE units, and a monomer having a hydroxyl group-containing group or a carbonyl group-containing group, or a polymer containing TFE units and PAVE units and having a hydroxyl group-containing group or a carbonyl group-containing group at the end of the main chain, with the former polymer being more preferred. Polymer (1) preferably contains 94 to 98.49 mol% of TFE units, 1.5 to 3 mol% of PAVE units, and 0.01 to 3 mol% of units based on the monomer, relative to the total units. Furthermore, the monomer is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic acid anhydride (also known as Hymic anhydride; hereinafter also referred to as "NAH"). A specific example of polymer (1) is the polymer described in International Publication No. 2018 / 16644.

[0018] The polymer (2) consists only of TFE units and PAVE units, and preferably contains 95 to 98 mol% TFE units and 2 to 5 mol% PAVE units relative to the total monomer units. The PAVE unit content in polymer (2) is preferably 2.1 mol% or more, and more preferably 2.2 mol% or more, relative to the total monomer units. Furthermore, polymer (2) not having oxygen-containing polar groups means that the number of carbon atoms constituting the polymer main chain is 1 × 10⁶. 6 This means that the number of oxygen-containing polar groups per polymer is less than 500. The number of oxygen-containing polar groups is preferably 100 or less, and more preferably less than 50. The lower limit of the number of oxygen-containing polar groups is usually 0. Polymer (2) may be produced using polymerization initiators, chain transfer agents, etc., that do not generate oxygen-containing polar groups as terminal groups of the polymer chain, or it may be produced by fluorinating an F polymer having oxygen-containing polar groups. Examples of fluorination methods include using fluorine gas (see Japanese Patent Publication No. 2019-194314, etc.).

[0019] The F powder in the present invention is a powder containing an F polymer, and the content of the F polymer in the F powder is preferably 80% by mass or more, and more preferably 100% by mass. One type of F powder may be used, or two or more types may be used. When two types of F powder are used, it is preferable to use a combination of a first powder of PTFE and a second powder of F polymer containing PAVE units, with PAVE units present in an amount of 1 to 5 mol% of the total units, and having a melting temperature of 260 to 320°C. In this case, the proportion of the second powder to the total of the first and second powders is preferably 25% by mass or less, and more preferably 15% by mass or less. Furthermore, the proportion in this case is preferably 0.1% by mass or more, and more preferably 1% by mass or more. This dispersion not only offers excellent dispersion stability, handling properties, and long-term storage capabilities, but also facilitates the production of adhesive fired products with superior physical properties based on PTFE. In this case, it is preferable that the D50 of the first powder is 0.1 to 1 μm and the D50 of the second powder is 0.1 to 1 μm, or that the D50 of the first powder is 0.1 to 1 μm and the D50 of the second powder is 1 to 4 μm. The second powder may be the powder of polymer (1) or the powder of polymer (2), and it is preferable that it be the powder of polymer (1).

[0020] F powder may contain polymers or inorganic substances different from F polymer. Examples of different polymers include aromatic polyesters, polyamide-imides, polyimides, polyphenylene ethers, polyphenylene oxides, and maleimides. Inorganic materials include silicon dioxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda-alumina, magnesium oxide, zinc oxide, titanium oxide, etc.), boron nitride, and magnesium metasilicate (steatite). F powder containing a polymer or inorganic substance different from the F polymer preferably has a core-shell structure in which the F polymer is the core and the polymer or inorganic substance different from the F polymer is the shell, or a core-shell structure in which the F polymer is the shell and the polymer or inorganic substance different from the F polymer is the core. Such F powder can be obtained, for example, by bonding powder of the F polymer and powder of a polymer or inorganic substance different from the F polymer by collision or aggregation.

[0021] The D50 of the F powder is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 8 μm or less. The D50 of the F powder is preferably 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 1 μm or more. In particular, when the F polymer is polymer (1), the D50 of the F powder in this dispersion is preferably 1 to 8 μm. When the F powder contains a first powder and a second powder, the D50 of the F powder is preferably 0.1 to 5 μm, and more preferably 0.1 to 3 μm. The specific surface area of ​​F powder ranges from 1 to 8 m². 2 / g is preferred, 1 to 3m 2 / g is more preferable. Even if the D50 is small and the F powder is in the form of fine particles, the dispersion tends to have excellent dispersion stability, handling properties, and long-term storage properties due to the mechanism of action described above.

[0022] The polyoxyalkylene-modified dimethylsiloxane in the present invention is an organopolysiloxane having a polyoxyalkylene structure as a hydrophilic group and a polydimethylsiloxane structure as a hydrophobic group, and is preferably a linear polymer. The weight-average molecular weight of the polyoxyalkylene-modified dimethylsiloxane is preferably 3000 or less, more preferably 2500 or less, and more preferably 2000 or less. It is also preferably 100 or more, and more preferably 500 or more. In this case, due to the above-described mechanism of action, the dispersion tends to exhibit excellent dispersion stability, handling properties, and long-term storage capabilities. Furthermore, its excellent thermal decomposition properties make it easier to improve the physical properties of the calcined product. The number-average molecular weight of polyoxyalkylene-modified dimethylsiloxane is preferably 3000 or less, more preferably 1500 or less. The number-average molecular weight is preferably 100 or more, more preferably 500 or more.

[0023] The molecular weight dispersion of polyoxyalkylene-modified dimethylsiloxane is preferably less than 2.0, and more preferably 1.8 or less. The lower limit of molecular weight dispersion is preferably greater than 1.0. The HLB value of polyoxyalkylene-modified dimethylsiloxane is between 1 and 18, preferably 3 or higher, more preferably 6 or higher, even more preferably 10 or higher, and particularly preferably 12 or higher. The HLB value is preferably 16 or lower, and more preferably 15 or lower. The static surface tension of the polyoxyalkylene-modified dimethylsiloxane is preferably 28 mN / m or less, more preferably 26 mN / m or less. The static surface tension is preferably 15 mN / m or more, more preferably 20 mN / m or more. The dynamic surface tension of the polyoxyalkylene-modified dimethylsiloxane is preferably 40 mN / m or less, more preferably 35 mN / m or less, and preferably 20 mN / m or more.

[0024] Polyoxyalkylene-modified dimethylsiloxane has a main chain of dimethylpolysiloxane units (-(CH3)2SiO 2 / 2 It may have -), may have dimethylpolysiloxane units in the side chain, and may have dimethylpolysiloxane units in both the main chain and the side chain. The polyoxyalkylene-modified polydimethylsiloxane is preferably a polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in the main chain and oxyalkylene groups in the side chains, or a polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in the main chain and oxyalkylene groups at the ends of the main chain.

[0025] The former, polyoxyalkylene-modified polydimethylsiloxane, is given by formula -(R 1 )(R2 )SiO 2 / 2 preferably contains a diorganosiloxane unit represented by - R in the formula 1 represents an alkyl group, and is preferably a methyl group. R in the formula 2 represents a group having a polyoxyalkylene group, and is of the formula -X 2 -O-(Y 2 ) n -Z 2 preferably a group represented by (wherein X 2 represents an alkylene group, Y 2 represents a polyoxyalkylene group, Z 2 represents a hydrogen atom, an alkyl group or an acyl group, and n represents an integer of 2 to 100, respectively.). Examples of X 2 include an ethylene group, a propylene group, and a butylene group. Examples of Y 2 include an oxyethylene group and an oxypropylene group. Examples of the alkyl group or acyl group for Z 2 include a methyl group and an acetyl group.

[0026] Further, the oxyalkylene group contained in the polyoxyalkylene-modified dimethylsiloxane may consist of only one type of oxyalkylene group, or may consist of two or more types of oxyalkylene groups. In the latter case, different types of oxyalkylene groups may be connected in a random form, or may be connected in a block form. In the polyoxyalkylene-modified polydimethylsiloxane, the polymerization degree of the oxyalkylene group (the number of repeating units of the oxyalkylene group) is preferably 2 or more. The polymerization degree is preferably 100 or less, more preferably 50 or less, and even more preferably 20 or less.

[0027] In polyoxyalkylene-modified polydimethylsiloxane, the degree of polymerization of dimethylsiloxane (number of repeating dimethylsiloxane units) is preferably 2 or higher. This degree of polymerization is preferably 100 or less, more preferably 50 or less, and even more preferably 25 or less. In this case, the dispersion tends to exhibit excellent dispersion stability, handling properties, and long-term storage capabilities. Specific examples of polyoxyalkylene-modified polydimethylsiloxanes include "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by Bic Chemie Japan), "KF-6011", and "KF-6043".

[0028] The liquid dispersion medium in the present invention is preferably a polar compound that is liquid at atmospheric pressure and 25°C, and more preferably at least one selected from water, amides, ketones, and esters. The boiling point of the liquid dispersion medium is preferably in the range of 50 to 240°C. The liquid dispersion medium may be used alone or in combination of two or more types. Using such a liquid dispersion medium tends to result in a dispersion with excellent dispersion stability, handling properties, and long-term storage capabilities.

[0029] Specific examples of liquid dispersion media include water, N,N-dimethylformamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N-methyl-2-pyrrolidone, γ-butyrolactone, cyclohexanone, cyclopentanone, butyl acetate, methyl isopropyl ketone, and methyl ethyl ketone. The liquid dispersion medium may contain other solvents. Other solvents include aliphatic or aromatic hydrocarbons such as toluene; glycols; glycol ethers such as glycol monoalkyl ethers and glycol monoaryl ethers; and glycol acetates such as glycol monoalkyl ether acetates and glycol monoaryl ether acetates.

[0030] The liquid dispersion medium preferably contains water. The water content in the liquid dispersion medium is preferably 80% by mass or more, and more preferably 100% by mass. When the liquid dispersion medium contains water, the pH of the dispersion is preferably 6 to 12, and more preferably 7 to 11. In this case, the dispersion tends to have excellent long-term storage properties. To adjust the pH of this dispersion, it may contain ammonia or amines. Specific examples of amines include alkanolamines such as ethanolamine, secondary amines such as dimethylamine and diethylamine, tertiary amines such as triethylamine and N-methylmorpholine, and quaternary ammonium hydroxides such as tetramethylammonium hydroxide and tetramethylammonium hydroxide.

[0031] The content of F polymer in this dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 25% by mass or more. The content of F polymer is preferably 70% by mass or less, and more preferably 50% by mass or less. In this case, the dispersion tends to have excellent dispersion stability, handling properties, and long-term storage properties, and it is easy to produce calcined products of any thickness from this dispersion. The content of polyoxyalkylene-modified polydimethylsiloxane in this dispersion is preferably 30% by mass or less, and more preferably 15% by mass or less. The content of polyoxyalkylene-modified polydimethylsiloxane is preferably 0.1% by mass or more, and more preferably 1% by mass or more. In this case, the dispersion tends to have excellent dispersion stability, handling properties and long-term storage properties, and the calcined product obtained from this dispersion tends to have excellent physical properties such as electrical properties or surface smoothness. In the present invention, the content of the liquid dispersion medium is preferably 30 to 90% by mass, and more preferably 50 to 80% by mass.

[0032] The viscosity of this dispersion is preferably 5 mPa·s or higher, more preferably 10 mPa·s or higher. The viscosity of this dispersion is preferably 2000 mPa·s or lower, more preferably 1000 mPa·s or lower, even more preferably less than 400 mPa·s, and particularly preferably less than 300 mPa·s. In this case, the dispersion has excellent coating properties and readily forms fired products (polymer layers, etc.) of any desired thickness. Furthermore, when this dispersion is within this viscosity range, the physical properties of the F polymer tend to be highly expressed in the fired products obtained from it. The thixotropy of this dispersion is preferably 1.0 or higher. A thixotropy of 3.0 or lower is preferable, and 2.0 or lower is more preferable. In this case, the dispersion exhibits excellent coating properties and homogeneity, and is more likely to produce a denser fired product (such as a polymer layer).

[0033] In this dispersion, the component sedimentation rate is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. Here, the component sedimentation rate is a value calculated using the following formula based on the total height of the dispersion in the screw-cap tube and the height of the sedimentation layer (dispersion layer) before and after standing, when 18 mL of this dispersion is placed in a screw-cap tube with an internal volume of 30 mL and left to stand at 25°C for 14 days. Component sedimentation rate (%) = (height of sedimentation layer) / (total height of the dispersion) × 100 If no settling layer is observed after standing and there is no change in the state, the overall height of the dispersion will be considered unchanged, and the component settling rate will be considered 100%.

[0034] This dispersion may also contain other resins (polymers) different from polymer F. Even when other resins are included, this dispersion tends to exhibit excellent dispersion stability, handling properties, and long-term storage capabilities. The other resin may be a thermosetting resin or a thermoplastic resin. Other resins include epoxy resins, maleimide resins, urethane resins, elastomers, polyimides, polyamic acids, polyamide-imides, polyphenylene ethers, polyphenylene oxides, liquid crystal polyesters, and fluoropolymers other than F polymers. As for other resins, aromatic polymers are preferred. When this dispersion contains an aromatic polymer, the fired product formed from this dispersion tends to have excellent adhesion, low linear expansion, and UV absorption properties.

[0035] The aromatic polymer is preferably an aromatic elastomer such as aromatic polyimide, aromatic polyamideimide, aromatic maleimide, or styrene elastomer, or an aromatic polyamic acid; more preferably an aromatic elastomer such as aromatic polyimide, aromatic polyamideimide, a precursor of aromatic polyamideimide, aromatic maleimide, polyphenylene ether, or styrene elastomer, and even more preferably an aromatic polyimide or an aromatic polyamic acid. Aromatic polyimides may be thermoplastic or thermosetting. Thermoplastic polyimides refer to polyimides in which the imidation process is complete and no further imidation reactions occur.

[0036] Specific examples of aromatic polyimides include the "NeoPrim®" series (manufactured by Mitsubishi Gas Chemical Company), the "Spixeria®" series (manufactured by Somar), the "Q-PILON®" series (manufactured by PI Technical Research Institute), the "WINGO" series (manufactured by Wingo Technology Co., Ltd.), the "Tomide®" series (manufactured by T&K TOKA Co., Ltd.), the "KPI-MX" series (manufactured by Kawamura Sangyo Co., Ltd.), and the "Yupia®-AT" series (manufactured by Ube Industries, Ltd.). Specific examples of aromatic polyamide-imides and their precursors include "HPC-1000" and "HPC-2100D" (both manufactured by Showa Denko Materials Co., Ltd.). Examples of styrene elastomers include styrene-butadiene copolymers, hydrogenated styrene-butadiene copolymers, hydrogenated styrene-isoprene copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, hydrogenated styrene-butadiene-styrene block copolymers, and hydrogenated styrene-isoprene-styrene block copolymers.

[0037] This dispersion may further contain inorganic fillers. In this case, the calcined product produced from this dispersion tends to exhibit excellent electrical properties and low linear expansion. The inorganic filler is preferably a nitride filler or an inorganic oxide filler, more preferably a silicate filler such as boron nitride filler, beryllium oxide filler, silica filler, wollastonite filler, or talc filler, or metal oxide fillers such as cerium oxide filler, aluminum oxide filler, magnesium oxide filler, zinc oxide filler, or titanium oxide filler, with silica filler being even more preferred. It is preferable that at least a portion of the surface of the inorganic filler is surface-treated with a silane coupling agent (such as 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-isocyanatetopropyltriethoxysilane, etc.).

[0038] The D50 of the inorganic filler is preferably 20 μm or less, and more preferably 10 μm or less. The D50 is preferably 0.01 μm or more, and more preferably 0.1 μm or more. The inorganic filler may be granular, needle-shaped (fibrous), or plate-shaped. Specific shapes of the inorganic filler include spherical, flaky, layered, leaf-shaped, kernel-shaped, columnar, comb-shaped, equiaxed, leaf-shaped, mica-like, block-shaped, plate-shaped, wedge-shaped, rosette-shaped, reticulated, and prismatic. Inorganic fillers may be used individually or in combination of two or more types.

[0039] Suitable examples of inorganic fillers include silica fillers (such as the "AdmaFine®" series from Admatex Co., Ltd.), zinc oxide fillers surface-treated with esters such as propylene glycol dicaprate (such as the "FINEX®" series from Sakai Chemical Industry Co., Ltd.), spherical fused silica fillers (such as the "SFP®" series from Denka Co., Ltd.), titanium oxide fillers coated with polyhydric alcohols and inorganic materials (such as the "Typeque®" series from Ishihara Sangyo Co., Ltd.), and rutile-type titanium oxide fillers surface-treated with alkylsilane. Examples include the "JMT(registered trademark)" series from Teika Corporation, hollow silica fillers (such as the "E-SPHERES" series from Taiheiyo Cement Corporation, the "Silinax" series from Nippon Steel Mining Co., Ltd., and the "Ecocos Filler" series from Emerson & Cumming Co., Ltd.), talc fillers (such as the "SG" series from Nippon Talc Corporation), steatite fillers (such as the "BST" series from Nippon Talc Corporation), and boron nitride fillers (such as the "UHP" series from Showa Denko Corporation and the "Denka Boron Nitride" series ("GP" and "HGP" grades) from Denka Corporation).

[0040] In addition to the components mentioned above, this dispersion may also contain additives such as thixotropic agents, defoaming agents, silane coupling agents, dehydrating agents, plasticizers, weathering agents, antioxidants, heat stabilizers, lubricants, antistatic agents, whitening agents, colorants, conductive agents, mold release agents, surface treatment agents, viscosity modifiers, flame retardants, and organic fillers. It is preferable that this dispersion does not contain fluorinated surfactants. Due to the mechanism of action described above, this dispersion tends to have excellent dispersion stability even without containing fluorinated surfactants. If the dispersion contains an aromatic polymer, the content of the aromatic polymer in the dispersion is preferably 0.1 to 20% by mass, and more preferably 1 to 10% by mass. If the dispersion contains an inorganic filler, the inorganic filler content in the dispersion is preferably 1 to 50% by mass, and more preferably 5 to 40% by mass.

[0041] A preferred embodiment of this dispersion is one which further includes at least one nonionic surfactant (hereinafter also referred to as "other surfactant") selected from the group consisting of ester-type surfactants, ether-type surfactants, ester-ether-type surfactants, alkanolamide-type surfactants, alkyl glycooxides, and higher alcohols. In this case, the dispersion stability of this dispersion during long-term storage is more easily improved. The reason for this is not entirely clear, but it is thought that the dispersive effect of the highly stable other surfactant on the F powder increases relatively over time. In particular, this mechanism of action is easily enhanced in this dispersion where the liquid dispersion medium is water. If the dispersion contains other surfactants, the content of the other surfactants in the dispersion is preferably 0.1 to 15% by mass, and more preferably 1 to 10% by mass. In this case, the ratio of the content of the other surfactants to the content of the surfactant in the dispersion is preferably 0.1 to 10.

[0042] Other surfactants are preferably ether-type surfactants or ester-ether-type surfactants, more preferably glycol monoalkyl ethers, glycol monoaryl ethers, glycol monoalkyl ether acetates, or glycol monoaryl ether acetates, and even more preferably glycol monoalkyl ethers. The glycol monoalkyl ether is preferably polyoxyethylene glycol monoalkyl ether. The number of oxyethylene units (-OCH2CH2-) contained in the polyoxyethylene ethylene glycol is preferably 1 to 10, and the monoalkyl ether group is preferably highly branched.

[0043] Other specific examples of surfactants include polyethylene glycol decyl ether, polyethylene glycol undecyl ether, polyethylene glycol dodecyl ether, polyethylene glycol tridecyl ether, polyethylene glycol tetradecyl ether, triethylene glycol monomethyl ether, polyethylene glycol trimethyl nonyl ether, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, dipropylene glycol monobutyl ether, triethylene glycol monomethyl ether, tripropylene glycol monobutyl ether, propylene glycol monophenyl ether, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.

[0044] Other suitable examples of surfactants include the "Tergitol" series (manufactured by Dow Chemical, such as "Tergitol TMN-100X"), "Lutensol T08", "Lutensol XL70", "Lutensol XL80", "Lutensol XL90", "Lutensol XP80", and "Lutensol M5" (all manufactured by BASF), "Newcol 1305", "Newcol 1308FA", and "Newcol 1310" (all manufactured by Nippon Emulsifier Co., Ltd.), and "Leocol TDN-90-80" and "Leocol SC-90" (both manufactured by Lion Specialty Chemicals).

[0045] The present invention also provides a powder dispersion (hereinafter also referred to as "the second dispersion") having a viscosity of less than 400 mPa·s, comprising a tetrafluoroethylene polymer powder, a polyoxyalkylene-modified polydimethylsiloxane containing dimethylsiloxane units in the main chain and oxyalkylene groups in the side chains, or a polyoxyalkylene-modified polydimethylsiloxane containing dimethylsiloxane units in the main chain and oxyalkylene groups at the ends of the main chain, and a liquid dispersion medium containing at least water. In such a powder dispersion, the respective embodiments of F powder and polyoxyalkylene-modified polydimethylsiloxane are the same as those in the present dispersion, including their preferred ranges. In such a powder dispersion, the liquid dispersion medium, which contains at least water, may consist of water alone, or it may consist of water and another liquid dispersion medium. Such other liquid dispersion medium is the same as in the embodiment in this dispersion. Furthermore, the various components of such powder dispersions are the same as those of the aforementioned dispersion, including their preferred ranges. In particular, the viscosity of such powder dispersions is preferably 5 mPa·s or more and less than 400 mPa·s, and more preferably 10 mPa·s or more and less than 300 mPa·s.

[0046] Preferably, the weight-average molecular weight of the polyoxyalkylene-modified polydimethylsiloxane, which contains dimethylsiloxane units in the main chain and has oxyalkylene groups in the side chains, or the polyoxyalkylene-modified polydimethylsiloxane, which contains dimethylsiloxane units in the main chain and has oxyalkylene groups at the ends of the main chain, is 3000 or less, and the HLB value calculated from the Griffin formula is 1 to 18. The preferred ranges for weight-average molecular weight and HLB value are the same as described above.

[0047] In such a powder dispersion, the liquid dispersion medium, which contains at least water, may consist of water alone, or it may consist of water and another liquid dispersion medium. Such other liquid dispersion medium is the same as in the embodiment in this dispersion. Furthermore, the composition of such powder dispersions, including their preferred ranges, is the same as that of the present dispersion. In particular, the viscosity of such powder dispersions is preferably 5 mPa·s or more and less than 400 mPa·s, and preferably 10 mPa·s or more and less than 300 mPa·s.

[0048] The first dispersion or the second first dispersion can be prepared by mixing F powder, the polyoxyalkylene-modified polydimethylsiloxane, a liquid dispersion medium, and other surfactants if necessary. Preferably, it is prepared by mixing F powder with a liquid composition containing the polyoxyalkylene-modified polydimethylsiloxane, a liquid dispersion medium, and other surfactants if necessary. If the first dispersion or the second first dispersion contains two or more types of F powder, the first dispersion or the second first dispersion may be produced by mixing a mixture of the two or more types of F powder with a liquid composition containing the polyoxyalkylene-modified polydimethylsiloxane and a liquid dispersion medium, or by mixing a liquid composition containing F powder, the polyoxyalkylene-modified polydimethylsiloxane, a liquid dispersion medium and optionally other surfactants with a liquid composition containing different types of F powder and a liquid dispersion medium, with the latter method being preferred. In the latter method, the liquid composition comprising different types of F powder and a liquid dispersion medium may further contain the polyoxyalkylene-modified polydimethylsiloxane or other surfactants.

[0049] By coating the surface of the substrate with this dispersion and heating it to produce a calcined product of the F polymer, a composite material having the substrate and the calcined product of the F polymer can be obtained. Specific examples of composites include laminates having a substrate and a polymer layer containing F polymer (hereinafter also referred to as "F layer") (hereinafter also referred to as "this laminate"), fibers sized with F polymer, prepregs containing fibers sized with F polymer and a matrix resin, and fiber-reinforced composite materials formed from such prepregs.

[0050] If the substrate is in sheet form, this dispersion can be coated onto the surface of the sheet substrate to form a liquid film, this liquid film can be heated to remove the liquid dispersion medium and form a dry film, and then the dry film can be heated to bake the F polymer, thereby obtaining this laminate having the F layer on the surface of the sheet substrate. Examples of sheet substrates include metal substrates such as metal foils made of copper, nickel, aluminum, titanium, or their alloys, heat-resistant resin films, and prepregs which are precursors of fiber-reinforced resin substrates. The heat-resistant resin film is a film containing one or more heat-resistant resins such as polyimide, polyarylate, polysulfone, polyallylsulfone, polyamide, polyetheramide, polyphenylene sulfide, polyallyl ether ketone, polyamide-imide, liquid crystal polyester, liquid crystal polyesteramide, and F polymer, and may be a single-layer film or a multi-layer film. PTFE, PFA, and FEP are preferred as F polymers included in the heat-resistant resin film.

[0051] The method for coating the surface of the sheet substrate with this dispersion can be any method that forms a stable liquid film, or wet film, consisting of this dispersion on the surface of the sheet substrate. Examples include coating, droplet dispensing, and immersion, with coating being preferred. When drying the liquid coating, the coating is heated to a temperature at which the liquid dispersion medium volatilizes, forming a dried coating on the surface of the sheet substrate. The heating temperature is preferably 50°C or less above the boiling point of the liquid dispersion medium, and more preferably below the azeotrope. The specific drying temperature is preferably between 70 and 200°C. Air may be blown in during the step of removing the liquid dispersion medium. During drying, the liquid dispersion medium does not necessarily need to be completely evaporated; it is sufficient to evaporate it to the extent that the layer shape after retention is stable and the self-supporting film can be maintained.

[0052] The firing temperature for F polymer is preferably 380°C or lower. The heating described above may be carried out under either atmospheric pressure or reduced pressure. Furthermore, the heating atmosphere may be any of the following: an oxidizing gas atmosphere such as oxygen gas, a reducing gas atmosphere such as hydrogen gas, or an inert gas atmosphere such as helium gas, neon gas, argon gas, or nitrogen gas. The heating time is preferably 0.1 to 30 minutes, and more preferably 0.5 to 20 minutes.

[0053] The thickness of the F layer is preferably 0.1 to 150 μm. Specifically, when the sheet substrate is a metal foil, the thickness of the F layer is preferably 1 to 30 μm. When the sheet substrate is a heat-resistant resin film, the thickness of the F layer is preferably 1 to 150 μm. The peel strength between the F layer and the sheet substrate is preferably 10 N / cm or more, and more preferably 15 N / cm or more. The peel strength is preferably 100 N / cm or less. Using this dispersion, such a laminate can be easily formed without impairing the physical properties of the F polymer in the F layer.

[0054] This dispersion may be applied to only one surface of the sheet substrate, or to both surfaces of the sheet substrate. In the former case, a laminate is obtained having the sheet substrate and an F layer on one surface of the sheet substrate, while in the latter case, a laminate is obtained having the sheet substrate and an F layer on both surfaces of the sheet substrate. The latter laminate is less prone to warping and therefore has superior handling properties during processing. The laminate having an F layer on both surfaces of the substrate layer is preferably obtained by immersing the substrate in the dispersion to apply the dispersion to both surfaces of the substrate, and then heating it by passing it through a firing furnace. More specifically, it is more preferable to immerse the substrate in the dispersion, and then heat it by passing it through a firing furnace while removing the substrate from the dispersion. It is preferable that the direction in which the substrate is lifted and passed through the firing furnace is vertically upward. In this case, a smooth F layer is easily formed. After lifting the substrate vertically upward, it may be further heated while being pulled vertically downward, or it may be pulled down without heating and the substrate removed. Furthermore, the amount of this dispersion applied to the substrate can be adjusted by passing the substrate, to which the dispersion has adhered, between a pair of rolls. Such laminates can be suitably manufactured using an apparatus having a dip coater and a firing furnace. A vertical firing furnace is one example of such an apparatus. Another example of such an apparatus is a glass cloth coating apparatus manufactured by Tabata Machinery Industry Co., Ltd. Specific examples of this laminate include a metal-clad laminate having a metal foil and an F layer on at least one surface of the metal foil, and a polyimide film and a multilayer film having an F layer on both surfaces of the polyimide film.

[0055] Because the aforementioned laminate has an F layer with excellent electrical properties, it is suitable as a printed circuit board material. Specifically, it can be used in the manufacture of printed circuit boards as a flexible metal-clad laminate or a rigid metal-clad laminate, and is particularly suitable for use in the manufacture of flexible printed circuit boards as a flexible metal-clad laminate. In the manufacturing of such printed circuit boards, an interlayer insulating film may be formed on the transmission circuit, a solder resist may be laminated on the transmission circuit, or a coverlay film may be laminated on the transmission circuit. These interlayer insulating films, solder resists, and coverlay films may be formed using this dispersion. Furthermore, this laminate is also useful as a carrier film for forming ceramic green sheets, a carrier film for forming secondary batteries, a carrier film for forming solid polymer electrolyte membranes, and a carrier film for forming catalysts for solid polymer electrolyte membranes.

[0056] The laminate of the F layer and the substrate is useful for antenna components, printed circuit boards, aircraft parts, automotive parts, sports equipment, food industry products, heat dissipation components, paints, cosmetics, etc. In printed circuit boards, it can be used as a new printed circuit board material to replace conventional glass epoxy boards in order to prevent temperature rise in printed circuit boards with high density of electronic components. Specifically, it is useful as wire insulation for aircraft wires, enameled wire insulation for motors in electric vehicles, separation membranes, electrode binders for lithium secondary batteries or fuel cells, sliding members, tools, blades for wind turbines, wind power generation equipment, and aircraft, electrical insulation tapes, insulating tapes for oil drilling, printed circuit board materials, copy rolls, furniture, car dashboards, covers for home appliances, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts for centrifugal pumps, hydrocarbon, chemical and water supply pumps, boilers, hoppers, pipes, ovens, baking molds, chutes, dies, toilets, container insulation, power devices, transistors, thyristors, rectifiers, transformers, power MOS FETs, CPUs, heat sinks, and metal heat sinks. Examples of separation membranes include microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, and gas separation membranes. Examples of sliding components include load bearings, sliding shafts, valves, bearings, bushings, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, and food transport belts. Examples of tools include shovels, files, drills, and saws. More specifically, it is useful as a sealing material for processing machines, vacuum ovens, and plasma processing equipment that perform heat treatment under low oxygen conditions, such as for the casings of personal computers and displays, electronic device materials, and the interior and exterior of automobiles, as well as for heat dissipation components in processing units such as sputtering and various dry etching equipment.

[0057] Furthermore, this dispersion can be used to impregnate and dry coils used in the insulating layer of printed circuit boards, thermal interface materials, power module substrates, and power devices such as motors to form a heat-conductive, heat-resistant coating layer. It can also be used to bond ceramic and metal parts together in automotive engines, to provide corrosion resistance to heat exchangers and their constituent fins or tubes, and to coat the inside and outside of glass containers. It is particularly suitable for coatings that provide impact resistance. Examples of glass containers include vials, syringes, syringes with needles and cartridge-type syringes, and ampoules.

[0058] Furthermore, this dispersion can be used as a binder material for electrodes, a coating material for separators, and a coating material for positive or negative electrodes in electrochemical devices equipped with electrodes, such as secondary batteries like lithium-ion batteries, primary batteries like lithium batteries, radical batteries, solar cells, especially dye-sensitized solar cells, fuel cells, capacitors like lithium-ion capacitors, hybrid capacitors, and electric double-layer capacitors, various capacitors like aluminum electrolytic capacitors and tantalum electrolytic capacitors, electrochromic elements, electrochemical switching elements, and various electrochemical sensors. When used as a coating material, it is preferable that the dispersion contains water as the liquid dispersion medium.

[0059] Furthermore, F powder itself may be used as the coating material. In this case, F powder may be used alone as the coating material, or it may be used in combination with other materials, such as by mixing F powder with other materials (other resins, inorganic fillers, etc., which may be contained in the dispersion described above). In this case, if the F polymer is polymer (1), the D50 of the F powder is preferably 1 to 8 μm or 10 to 40 μm.

[0060] Furthermore, this dispersion, which also contains conductive fillers, can be suitably used in applications requiring conductivity, such as in the field of printed electronics. Specifically, it can be used in the manufacture of conductive elements in printed circuit boards, sensor electrodes, displays, backplanes, RFID (radio frequency identification), solar power generation, lighting, disposable electronic devices, automotive heaters, electromagnetic (EMI) shielding, membrane switches, and the like. Furthermore, the fired product obtained from this dispersion can be used as an adhesive for bonding electronic components such as IC chips, resistors, and capacitors mounted on substrates in semiconductor devices, high-density substrates, and module components, as well as for bonding circuit boards to heat sinks and for bonding LED chips to substrates. In addition, the fired product can be used as a conductive bonding material (as an alternative to soldering) between circuit wiring and electronic components in the electronic component mounting process. It can also be used as an adhesive between ceramic and metal components in automotive engines. Furthermore, the fired product can be used for the applications described in paragraph

[0149] of International Publication No. 2016 / 017801.

[0061] If the base material is fiber, applying this dispersion to the surface of the fiber and evaporating the liquid dispersion medium will yield sized fiber with F polymer adhering to its surface. The F polymer adhering to the surface of the fiber is preferably a calcined product of the F polymer. Sizing-treated fibers with calcined F polymer adhering to the surface are obtained by applying this dispersion to the fibers, evaporating the liquid dispersion medium, and then heat-treating to calcine the F polymer. Heating for evaporation of the liquid dispersion medium and calcination of the F polymer can be done in the same way as the heating for forming the F layer described above. Examples of fibers include glass fibers such as E glass, D glass, L glass, S glass, T glass, Q glass, UN glass, NE glass, and spherical glass; organic fibers such as aramid fibers, polyolefin fibers, modified polyphenylene ether fibers, vinylon fibers, rayon fibers, polyester fibers, and natural fibers; and boron fibers, carbon fibers, and metal fibers, with carbon fibers being preferred.

[0062] Examples of carbon fibers include pitch-based, rayon-based, polyacrylonitrile (PAN)-based, single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon nanofibers, with acrylonitrile (PAN)-based being preferred. The fiber shape may be chopped strand, surfacing, roving, or any of these, such as mats, woven fabrics, or nonwoven fabrics. There are also no particular restrictions on the fiber length or cross-sectional shape. Sized fibers may be used as fiber bundles or as sheet-like reinforcing fiber materials. Sized fibers may be used as continuous fibers or as discontinuous fibers.

[0063] Fibers sized using this dispersion exhibit excellent adhesion to the matrix resin and high impregnation of the matrix resin into the fiber bundle. Therefore, prepregs and fiber-reinforced composite materials with excellent mechanical properties can be easily obtained from such fibers. Prepregs can be manufactured by impregnating sized fibers with a matrix resin or matrix resin composition, and then drying and semi-curing them. Preferred matrix resins include polysulfone, polyphenylsulfone, polyethersulfone, aromatic polyetherketone, polyetherimide, polyphenylene sulfide, and liquid crystal polyester. By laminating prepregs and heating the matrix resin while applying pressure to the laminate, a fiber-reinforced composite material can be obtained. The F polymer may also be fired during the heating of the matrix resin.

[0064] The fiber-reinforced composite material may be laminated with other substrates. Examples of other substrates include metal substrates, heat-resistant resin films, and prepregs, which are precursors to fiber-reinforced resin sheets. Such fiber-reinforced composite materials are suitable for applications requiring strength, abrasion resistance, chemical resistance, flame retardancy, and low vibration. Examples include exteriors, interiors, and structural components of transportation equipment such as automobiles, motorcycles, and aircraft; sliding parts such as gears and bearings; insulating parts; tension ropes; sports equipment such as rackets and bats; industrial machinery; robots; medical equipment components; oil drilling equipment; oil transport hoses; hydrogen tanks; hydrogen tank pressure vessels; wind turbine blades; liquid nitrogen tanks; rotating parts of motors; and interiors and exteriors of rotating parts of compressors.

[0065] By coating the surface of the substrate with the second dispersion and heating it to produce a calcined product of the F polymer, a composite having the substrate and the calcined product of the F polymer can be obtained. Examples of composites include those similar to the composite obtained from the dispersion described above, and their manufacturing method and applications are also the same as those for the composite obtained from the dispersion.

[0066] Although the method for producing the powder dispersion and composite of the present invention has been described above, the present invention is not limited to the configuration of the embodiments described above. For example, the powder dispersion of the present invention may have any other configuration added to the configuration of the above embodiment, or may be replaced with any configuration that performs a similar function. Furthermore, the method for producing the composite of the present invention may include additional steps for any other purpose in the configuration of the above embodiment, or may be replaced with any other step that performs a similar function. [Examples]

[0067] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. 1. Preparation of each component [powder] Powder 1: A powder (D50: 2.1 μm) consisting of polymer 1 (melting temperature: 300°C) containing TFE units, NAH units, and PPVE units in the following proportions: 97.9 mol%, 0.1 mol%, and 2.0 mol%, respectively. Powder 2: A powder (D50: 1.8 μm) consisting of polymer 2 (melting temperature 305°C) containing 97.5 mol% and 2.5 mol% of TFE units and PPVE units, respectively. Powder 3: Powder 3 (D50: 0.3 μm) made of non-thermally fused PTFE. Note that the main chain has 1 × 10⁻¹⁶ carbon atoms. 6 Polymer 1 has 1000 carbonyl group-containing groups per molecule, while Polymer 2 has 40.

[0068] [Surfactants] Surfactant 1: Polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in the main chain and oxyethylene groups in the side chains (weight-average molecular weight: 1600, dispersion: 1.5, HLB value: 13, static surface tension: 25 mN / m, dynamic surface tension of 0.1 mass% aqueous solution: 30 mN / m) Surfactant 2: Polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in the main chain and oxyethylene groups at the ends of the main chain (weight-average molecular weight: 1000, dispersion: 1.1, HLB value: 14, static surface tension: 25 mN / m, dynamic surface tension: 30 mN / m) Surfactant 3: Polyoxyalkylene-modified polydimethylsiloxane (weight-average molecular weight: 4000, dispersion degree: 2.1, HLB value: 16, static surface tension: 26 mN / m, dynamic surface tension: 35 mN / m)

[0069] Surfactant 4: Polyoxyalkylene group-containing polyorganosiloxane (weight-average molecular weight 1800, dispersion degree 1.9, HLB value: 8, static surface tension: 30 mN / m, dynamic surface tension: 42 mN / m) Surfactant 5: Polyoxyalkylene group-containing polyorganosiloxane (weight-average molecular weight 1700, dispersion degree 1.8, HLB value: 19, static surface tension: 27 mN / m, dynamic surface tension: 36 mN / m) Surfactant 6: Polyethylene glycol trimethylnonyl ether However, surfactants 4 and 5 are polyorganosiloxanes containing polyoxyalkylene groups, which are different from polyoxyalkylene-modified polydimethylsiloxanes. Also, surfactants 1 to 6 are all nonionic compounds. [Dispersion] A PTFE aqueous dispersion (AGC Corporation, "product code AD-911E") containing 60% by mass of a dispersion 1:powder 3 ratio.

[0070] 2. Example of powder dispersion manufacturing (Example 1) First, powder 1, surfactant 1, and aqueous ammonia were placed in a pot, and then zirconia balls were added. The pot was then turned at 150 rpm for 1 hour to prepare composition 1. Composition 1 and dispersion 1 were placed in another pot, and zirconia balls were added. The pot was then turned at 150 rpm for 1 hour to obtain powder dispersion 1 containing powder 1 (5 parts by mass), powder 3 (45 parts by mass), surfactant 1 (0.25 parts by mass), and aqueous ammonia (47.5 parts by mass), with a viscosity of 20 mPa·s and a pH of 10.

[0071] (Examples 2 to 6) Powder dispersions 2 to 6 were obtained in the same manner as in Example 1, except that the type of powder and the type of surfactant were changed as shown in Table 1 below. In Table 1, "〇" in the ammonia column means that the powder dispersion contains ammonia, and "―" means that the powder dispersion does not contain ammonia. (Example 7) First, powder 1, surfactant 1, and ammonia water were placed in a pot, and then zirconia balls were added. The pot was then rolled at 150 rpm for 1 hour to obtain a powder dispersion 7 containing powder 1 (40 parts by mass), surfactant 1 (2 parts by mass), and ammonia water (58 parts by mass), with a viscosity of 30 mPa·s and a pH of 10.

[0072] (Examples 8 and 9) Powder dispersions 8 and 9 were obtained in the same manner as in Example 7, except that the type of surfactant was changed as shown in Table 1 below. (Example 10) Powder dispersion 10 was obtained in the same manner as in Example 7, except that the type of surfactant was changed as shown in Table 1 below, and water was used instead of ammonia water. Furthermore, powder dispersions 1 to 3 showed less change in hue during long-term storage compared to powder dispersions 4 to 6. Powder dispersions 7 and 8 also showed less change in hue during long-term storage compared to powder dispersions 9 and 10.

[0073] [Table 1]

[0074] 3. Examples of manufacturing laminates (composites) A liquid film was formed on the surface of a long copper foil (18 μm thick) by applying powder dispersion 1 using a bar coater. Next, the copper foil with this liquid film was passed through a drying oven at 120°C for 5 minutes to dry it by heating and obtain a dried film. After that, the dry film was heated in a nitrogen oven at 380°C for 3 minutes. This produced a laminate 1 having copper foil and a polymer layer (5 μm thick) on its surface that contains a molten product of powder 1 and powder 3 as a fired product. Laminates 2 through 10 were manufactured in the same manner as laminate 1, except that powder dispersion 1 was replaced with powder dispersions 2 through 10.

[0075] 4. Evaluation 4-1. Dispersion stability of powder dispersions Each powder dispersion was stored in a container at 25°C for 24 hours, and its dispersibility was visually inspected. The dispersion stability was then evaluated according to the following criteria. The same criteria were used to evaluate dispersion stability after 60 days of storage. [Evaluation Criteria] ○: No aggregates are visible. △: Fine aggregates were visible adhering to the side wall of the container. They redispersed uniformly after light stirring. ×: Aggregates can be seen settling at the bottom of the container. Shearing and stirring will redisperse them uniformly.

[0076] 4-2. Antifoaming properties of powder dispersions During the preparation (manufacturing) of each powder dispersion, the time until foaming disappeared was observed, and the defoaming properties were evaluated according to the following criteria. [Evaluation Criteria] ○: Less than 3 hours △: 3 hours or more, less than 6 hours ×: More than 6 hours

[0077] 4-3. Surface smoothness of the laminate Light was shone onto each laminate from the polymer layer side, and the polymer layer was visually inspected from an oblique angle above to evaluate its surface smoothness according to the following criteria. [Evaluation Criteria] ○: The entire surface of the polymer layer is smooth. △: A bumpy pattern is observed in part of the polymer layer. ×: A bumpy pattern is visible throughout the polymer layer. The results for each method, along with the physical properties (viscosity, pH) of the powder dispersion, are shown in Table 2 below.

[0078] [Table 2]

[0079] (Example 11) First, powder 1, surfactant 1, surfactant 6, and ammonia water were placed in a pot, and then zirconia balls were added. The pot was then rotated at 150 rpm for 1 hour to obtain a powder dispersion 11() containing powder 1 (40 parts by mass), surfactant 1 (2 parts by mass), surfactant 6 (2 parts by mass), and ammonia water (56 parts by mass), with a viscosity of 30 mPa·s and a pH of 10. Laminate 11 was manufactured in the same manner as laminate 1, except that powder dispersion 1 was replaced with powder dispersion 11. The evaluation results for the dispersion stability, defoaming properties, and surface smoothness of powder dispersion 11 were all "○".

[0080] (Example 12) Using the same procedure as in Example 11, a powder dispersion 11 was obtained containing powder 1 (40 parts by mass), surfactant 1 (0.5 parts by mass), surfactant 6 (3.5 parts by mass), and aqueous ammonia (56 parts by mass), with a viscosity of 33 mPa·s and a pH of 10. Laminate 12 was manufactured in the same manner as laminate 1, except that powder dispersion 1 was replaced with powder dispersion 12. The evaluation results for dispersion stability, defoaming properties, and surface smoothness of powder dispersion 12 were all "○". Furthermore, the dispersion stability of powder dispersions 7, 11, and 12, stored at 25°C for 60 days, was "×", "〇", and "〇" in that order. [Industrial applicability]

[0081] The powder dispersion of the present invention exhibits excellent dispersion stability, handling properties, and long-term storage capabilities, and can be used in the production of composites such as laminates having physical properties based on F polymer, sizing-treated fibers, prepregs, fiber-reinforced composite materials, and other impregnated materials. The composite material of the present invention is useful as an antenna component, printed circuit board, aircraft component, automobile component, sports equipment, food industry products, paint, cosmetics, etc. Specifically, it is useful as a wire coating material for aircraft wires, separation membranes such as microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, and gas separation membranes, electrode binders for lithium secondary batteries or fuel cells, sliding members such as load bearings, sliding shafts, valves, bearings, gears, cams, belt conveyors, and food transport belts, tools such as shovels, files, drills, and saws, electrical insulating tape, insulating tape for oil drilling, printed circuit board material, copy rolls, furniture, automobile dashboards, covers for home appliances, boilers, hoppers, pipes, ovens, baking molds, chutes, dies, toilets, and container coating materials.

Claims

1. A powder dispersion comprising a tetrafluoroethylene polymer powder, a liquid dispersion medium, and a polyoxyalkylene-modified polydimethylsiloxane having a weight-average molecular weight of 3000 or less and an HLB value of 1 to 18 calculated from the Griffin formula.

2. The powder dispersion according to claim 1, wherein the static surface tension of the polyoxyalkylene-modified polydimethylsiloxane is 28 mN / m or less.

3. The powder dispersion according to claim 1 or 2, wherein the dynamic surface tension of the polyoxyalkylene-modified polydimethylsiloxane is 40 mN / m or less.

4. The powder dispersion according to any one of claims 1 to 3, wherein the HLB value of the polyoxyalkylene-modified polydimethylsiloxane is 10 to 16.

5. The powder dispersion according to any one of claims 1 to 4, wherein the molecular weight dispersion of the polyoxyalkylene-modified polydimethylsiloxane is less than 2.

0.

6. The powder dispersion according to any one of claims 1 to 5, wherein the degree of polymerization of the oxyalkylene group in the polyoxyalkylene-modified polydimethylsiloxane is 2 to 100, and the degree of polymerization of the dimethylsiloxane is 2 to 100.

7. The powder dispersion according to any one of claims 1 to 6, wherein the polyoxyalkylene-modified polydimethylsiloxane is a polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in its main chain and oxyalkylene groups in its side chains.

8. The powder dispersion according to any one of claims 1 to 6, wherein the polyoxyalkylene-modified polydimethylsiloxane is a polyoxyalkylene-modified polydimethylsiloxane having dimethylsiloxane units in its main chain and oxyalkylene groups at the ends of the main chain.

9. The powder dispersion according to any one of claims 1 to 8, wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer that contains units based on perfluoro(alkyl vinyl ether), with 1 to 5 mol% of the units based on perfluoro(alkyl vinyl ether) relative to the total units, and has a melting temperature of 260 to 320°C.

10. The powder dispersion according to any one of claims 1 to 9, wherein the powder comprises a first powder of polytetrafluoroethylene and a second powder of a tetrafluoroethylene polymer having a melting temperature of 260 to 320°C, and containing units based on perfluoro(alkyl vinyl ether), with the units based on perfluoro(alkyl vinyl ether) being 1 to 5 mol% of the total units, and the proportion of the second powder to the sum of the first and second powders is 25% by mass or less.

11. The powder dispersion according to any one of claims 1 to 10, further comprising at least one nonionic surfactant selected from the group consisting of ester-type surfactants, ether-type surfactants, ester-ether-type surfactants, alkanolamide-type surfactants, alkyl glycosides, and higher alcohols.

12. The powder dispersion according to any one of claims 1 to 11, wherein the liquid dispersion medium contains water.

13. The powder dispersion according to claim 12, wherein the pH of the powder dispersion is 6 to 12.

14. A powder dispersion having a viscosity of less than 400 mPa·s, comprising a tetrafluoroethylene polymer powder, a polyoxyalkylene-modified polydimethylsiloxane containing dimethylsiloxane units in the main chain and oxyalkylene groups in the side chains, or a polyoxyalkylene-modified polydimethylsiloxane containing dimethylsiloxane units in the main chain and oxyalkylene groups at the ends of the main chain, and a liquid dispersion medium containing at least water.

15. A method for producing a composite, comprising coating the surface of a substrate with a powder dispersion according to any one of claims 1 to 14, heating to produce a calcined product of the tetrafluoroethylene polymer, and obtaining a composite having the substrate and the calcined product.

Citation Information

Patent Citations

  • New fluororesin aqueous dispersion

    JP2009161616A

  • Fluoropolymer-containing sol-gel coating

    JP2012082437A

  • Flexible metal laminate sheet

    WO2014010968A1